2014
DOI: 10.14233/ajchem.2014.17908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Adsorption and Photocatalytic Degradation Efficiency of Different Catalysts on Removal of Methylene Blue

Abstract: The present study investigates the efficiency of adsorption and photodegradation catalyzed by TiO2, ZnO, CdS and Co3O4 on the removal of methylene blue dye, in different pH values (4, 6, 9 and 11). The photocatalytic degradation of methylene blue dye in aqueous catalysts TiO2, ZnO, CdS and Co3O4 suspension follows apparent after 0.5 h of photodegradation a first-order kinetics. The photodegradation efficiency of methylene blue was fast in the present condition (pH 11, pH 6, pH 6 and pH 4) and slower in (pH 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…The CFVP dissociation constant pK a has not been determined, but based on the analysis of dissociation constants of other organophosphorus pesticides it can be concluded that this pesticide is negatively charged at pH > 6, therefore it is better adsorbed at lower pH. For organic pollutants (e.g., azo dyes), similar conclusions were made by Alkaim et al (2014) [45]. At pH <6, strong dye adsorption was observed on TiO 2 particles as a result of electrostatic attraction of positively charged TiO 2 .…”
Section: Effect Of Ph On the Chlorfenvinphos Degradationmentioning
confidence: 75%
“…The CFVP dissociation constant pK a has not been determined, but based on the analysis of dissociation constants of other organophosphorus pesticides it can be concluded that this pesticide is negatively charged at pH > 6, therefore it is better adsorbed at lower pH. For organic pollutants (e.g., azo dyes), similar conclusions were made by Alkaim et al (2014) [45]. At pH <6, strong dye adsorption was observed on TiO 2 particles as a result of electrostatic attraction of positively charged TiO 2 .…”
Section: Effect Of Ph On the Chlorfenvinphos Degradationmentioning
confidence: 75%
“…Here, the effect of pH on MB photodegradation efficiency was studied at pH 5.5, 7.5, and 9.5. As shown in Figure 5c, the photodegradation efficiency of MB was significantly higher in alkaline conditions, which could be attributed to the greater interaction between the photocatalyst and MB (note that MB is a cationic compound) and to the high hydroxylation of the photocatalyst surface as a consequence of the large amount of hydroxyl ions, which translated to the more efficient formation of hydroxyl radicals [34][35][36]. More importantly, recycling experiments using ZnO-based micro/nanoferns at different pH demonstrated that in more acidic environments, the recyclability was significantly decreased, indicating that ZnO dissolution and photocorrosion increased.…”
Section: Adsorption Experimentsmentioning
confidence: 91%
“…The pH of the dye plays an important role in dye degradation, since, the adsorption capacity of dyes on the photo catalyst is an important factor. An increase in the rate of molecule decomposition is the result of an increase in the number of target molecules adsorbed onto a catalyst [27]. In this study, the effect of pH on the photocatalytic activity of CeO 2 nano particles (10 mg/L) during the MB degradation process with an initial concentration of 5 mg/L over a pH ranges 1-12 was studied.…”
Section: Degradation Of Mb Catalysed By Cerium Oxidementioning
confidence: 99%